Subchronic exposure to kalach 360 SL-induced endocrine disruption and ovary damage in female rats. (1st January 2018) - Hamdaoui, Latifa; Naifar, Manel; Rahmouni, Fatma; Harrabi, Bahira; Ayadi, Fatma; Sahnoun, Zouheir; Rebai, Tarek
Abstract: Kalach 360 SL (KL), glyphosate (G) surfactant-based herbicides, is a systemic herbicide effective against weeds. It was applied in agriculture in Tunisia and throughout the world, which can represent a risk to non-target organisms. The aim of this study was to investigate the morphological and biochemical aspects of ovary injury after exposure to KL. Female Wistar rats were divided into three groups: group 1 was used as a control; group 2 orally received 0.07 ml of KL, (126 mg of G/kg) and group 3 orally received 0.175 ml of KL (315 mg of G/kg) each day for 60 days. The subchronic exposure of KL induces impaired folliculogenesis, ovary development, decreased oestrogen secretion, promoted oxidative stress and impairments of ovary histological aspects. Histological finding shows necrosis cell, vacuolisation of follicles, dissociated oocytes and granulosa cell, associated with several atretic follicles. We conclude that KL induces endocrine disruption and ovary damage in female rats.